2017
DOI: 10.1093/annonc/mdx527
|View full text |Cite|
|
Sign up to set email alerts
|

Activity and safety of crizotinib in patients with advanced clear-cell sarcoma with MET alterations: European Organization for Research and Treatment of Cancer phase II trial 90101 ‘CREATE’

Abstract: EORTC 90101, EudraCT number 2011-001988-52, NCT01524926.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 17 publications
1
41
0
1
Order By: Relevance
“…The prospective clinical trial of an ALK inhibitor to treat rhabdomyosarcoma did not show clinical meaningful efficacy [108]. On the other hand, crizotinib, an ALK inhibitor which has been investigated to rhabodmyosarcoma with ALK expression above, is known as inhibiting other targets such as MET, and showed some clinical responses to clear cell sarcomas overexpressing MET [109]. For rare diseases, rare mutation-targeted therapies are pursued, and the importance of detecting targeted mutations precisely (including mutation types) is greater; the risk of misdiagnosis should also be considered [110].…”
Section: Whole-genome Sequencing For Precision Medicine For Sts Patientsmentioning
confidence: 99%
“…The prospective clinical trial of an ALK inhibitor to treat rhabdomyosarcoma did not show clinical meaningful efficacy [108]. On the other hand, crizotinib, an ALK inhibitor which has been investigated to rhabodmyosarcoma with ALK expression above, is known as inhibiting other targets such as MET, and showed some clinical responses to clear cell sarcomas overexpressing MET [109]. For rare diseases, rare mutation-targeted therapies are pursued, and the importance of detecting targeted mutations precisely (including mutation types) is greater; the risk of misdiagnosis should also be considered [110].…”
Section: Whole-genome Sequencing For Precision Medicine For Sts Patientsmentioning
confidence: 99%
“…The PFS with crizotinib in MET+ CCS was similar to results achieved with doxorubicin. 15 The NCT00557609, a phase 2 trial, has shown that disease control was obtained in 36% patients with tivantinib, a MET inhibitor. 16 Mir et al reported a case of metastatic CCS with myocardium metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In unusual cases, additional diagnostic work-up such as molecular pathological investigations are necessary to determine rare differential diagnoses. Early diagnosis is particularly important for a favorable outcome of CCS [7,10]. We recommend the performance of FISH or fusion analyses for EWS gene rearrangements in patients with atypical clinical courses or wild type mutated MUP.…”
Section: Dear Editorsmentioning
confidence: 99%